2000
DOI: 10.1002/j.2161-0029.2000.tb00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Perceived Self-Efficacy in Older Adults

Abstract: The purpose of this study was to examine predictors of seyeficacy in older adults, with physical activity, age, and sex as the predictor variables. Regression analyses revealed physical activity to be the only statistically signi$cant predictor of seyeficacy. Thesejndings may be of interest t o counselors who work with olderpeople.The population of the United States is rapidly aging. Life expectancies for men and women are increasing (U.S. Bureau of the Census, 1997), and the over-65 age group is projected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…This, in turn, may help generate an individual’s confidence to do something about their health status. However, physical activity should be personalized preventing people from becoming discouraged [26]. Thus, interventions to support resilience building in older adults should be framed within a model of fostering self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, may help generate an individual’s confidence to do something about their health status. However, physical activity should be personalized preventing people from becoming discouraged [26]. Thus, interventions to support resilience building in older adults should be framed within a model of fostering self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with higher self-efficacy may therefore choose to participate in a greater range of activities, including more difficult or unfamiliar activities, and may show greater persistence and employ strategies to overcome barriers to activity. Supporting this conjecture, cross-sectional research has shown that general and domain-specific self-efficacy are positively related to older adults' physical and social activity [5,14,15] . In addition, longitudinal studies have shown that higher baseline exercise self-efficacy is associated with greater exercise frequency at 6-month [16] and 12-month follow-ups [17] .…”
Section: Associations Of Pain Physical Symptoms and Self-efficacy Wmentioning
confidence: 73%
“…Associations of between-person general selfefficacy with activity have been shown [14,15] ; however, most previous cross-sectional [e.g., 5 , 17 ] and microlongitudinal [20,21] research has used activity-specific measures of self-efficacy. The finding that higher within-person general self-efficacy predicts greater activity is particularly notable because self-efficacy is most predictive of outcomes when measurement items are specifically related to the behavior or goal [13] .…”
Section: Within-person Self-efficacy and Activitymentioning
confidence: 99%
“…Exercise self-efficacy (ESE) was measured using Bandura’s ESE scale [ 30 , 44 ]. Bandura [ 30 ] developed a tool to purposely quantify self-efficacy, and this has been deployed in older adults finding that PA predicted self-efficacy, although not as much as age and gender [ 45 ]. Finally, the Short Questionnaire to Assess Health Enhancing Physical Activity (SQUASH) was provided to the participants to evaluate their self-reported PA level [ 44 , 46 ].…”
Section: Methodsmentioning
confidence: 99%